The Laurentide Ice Sheet in southern New England and New York during and at the end of the Last Glacial Maximum: a cosmogenic-nuclide chronology - A. Balter-Kennedy; J. M. Schaefer; G. Balco; M. A. Kelly; M. R. Kaplan; R. Schwartz; B. Oakley; N. E. Young; J. Hanley; A. M. Varuolo-Clarke (Climate of the Past, 2024)
We present 40 new 10 Be exposure ages of moraines and other glacial deposits left behind by the southeastern sector of the Laurentide Ice Sheet (LIS) in southern New England and New York, summarize the regional moraine record, and interpret the dataset in the context of previously published deglaciation chronologies. The regional moraine record spans the Last Glacial Maximum (LGM), with the outermost ridge of the terminal complex dating to ∼ 26–25 ka, the innermost ridge of the terminal complex dating to ∼ 22 ka, and a series of smaller recessional limits within ∼ 50 km of the terminal complex dating to ∼ 21–20.5 ka. The chronology generally agrees with independent age constraints from radiocarbon and glacial varves. A few inconsistencies between ages from cosmogenic-nuclide measurements and those from other dating methods are explained by geological scatter, where several bedrock samples and boulders from the outer terminal moraine exhibit nuclide inheritance, while some exposure ages of large moraines are likely affected by postdepositional disturbance. The exposure age chronology places the southeastern sector of the LIS at or near its maximum extent, from ∼ 26 to 21 ka, which is broadly consistent with the LGM sea-level lowstand, local and regional temperature indicators, and local summer insolation. The net change in LIS extent, represented by this chronology, occurred more slowly ( < 5 to 25 m yr −1 ) than the subsequent retreat through the rest of New England, consistent with a slow general rise in insolation and modeled summer temperature. We conclude that the major pulse of LIS deglaciation and accelerated recession, recorded by dated glacial deposits north of the moraines discussed here, did not begin until after atmospheric CO 2 increased around 18 ka, marking the onset of Termination I.